How uncertainty about judicial nominees can distort the confirmation process. (January 2017) - Sen, Maya; Spaniel, William
Why are judicial nominees allowed to refuse to answer questions about important issues that could come before the courts? We address this question by examining the information environment surrounding judicial nominations. Using the Supreme Court as our example, we formulate a model that departs from the existing literature by incorporating the fact that the Senate often does not know what type of candidate the President is trying to appoint. Our model shows when the President and Senate are ideologically divergent, low information about nominees' views results in the Senate occasionally rejecting acceptable nominees. However, when the President and Senate are ideologically close, the President benefits from leaving the process opaque—that is, allowing his nominees to avoid answering tough questions. Thus, even though low information can be costly to both parties, keeping the process nontransparent shields the President from being penalized for selecting more like-minded (and possibly extreme) judges.